Dampak kepemimpinan transformasional dan pelatihan terhadap employee well-being: Keadilan organisasional sebagai mediator - Mei Ie; Henny Henny; Atalya Fransiska; Viny Angellika; Zefanya Salsabilla (Universitas Kristen Maranatha, 2021)
The purpose of this study was to empirically examine the effect of transformational leadership and human resources training on employee well-being with organizational justice as a mediating variable. This study used purposive sampling. The sample consisted of 54 respondents who were employees, and the research data were analyzed using the SmartPLS version 3.3.2 software program. The results of this study indicated that transformational leadership and human resources training at the company have a significant and positive effect on employee well-being. This means that the better the transformational leadership is realized in the company, the higher the employee well-being in the company. However, based on the research results, organizational justice did not have a significant and negative effect on employee well-being. So that organizational justice cannot mediate the relationship between transformational leadership and human resources training for employee well-being. The implication of this research for companies in general is that companies can maintain and improve their employee well-being. Suggestions for the company, it is hoped that it can maintain and improve transformational leadership and conduct human resources training regularly and with good procedures to improve employee well-being in a company, because human capital is the one of the main capitals that it is important to be managed by the company.